Coming apart - Martin, Ann M., 1955- (Martin, Ann M., 1955- Main Street, 2010)
When Nikki's father left her family, she thought all of the screaming and fighting at home would be over, but when he returns, she calls on the support of her mother and friends to pull her through the difficult time.